Tiger Crisis: a Roadmap to Save This Critically Endangered Species - Ramakantha, V.; Kumar, Anil (Indian Forester, 2005)
All out efforts are to be made to save the Tiger (Panthera tigris tigris) as the animal is an icon of biodiversity. This paper offers a road map to save this critically endangered species. It is a myth that human beings can coexist with the tiger, as tigers need inviolate places. Voluntary rehabilitation of forest dwelling species, especially those inside tiger reserves, parks and sanctuaries thus becomes a priority issue. However, more than adequate compensation should be offered to forest dwellers in terms of guaranteed employment, and an enviable life style in their new surroundings. Wildlife and Forests needs to be declared a Priority Sector at the national level, and all efforts should be made to equip, train and empower forest personnel to tackle the organised wildlife criminals.